A paradoxical knowledge gap in science for critically endangered fishes and game fishes during the sixth mass extinction - Christopher S. Guy (Nature Portfolio, 2021)
Abstract Despite unprecedented scientific productivity, Earth is undergoing a sixth mass extinction. The disconnect between scientific output and species conservation may be related to scientists studying the wrong species. Given fishes have a high extinction rate, we assessed the paradox between scientific productivity and science needed for conservation by comparing scientific output created for critically endangered fishes and game fishes. We searched 197,866 articles (1964–2018) in 112 journals for articles on 460 critically endangered fishes, 297 game fishes, and 35 fishes classified as critically endangered and game fish—our analysis included freshwater and marine species. Only 3% of the articles in the final database were on critically endangered fishes; 82% of critically endangered fishes had zero articles. The difference between the number of articles on game fishes and critically endangered fishes increased temporally with more articles on game fishes during the extinction crisis. Countries with 10 or more critically endangered fishes averaged only 17 articles from 1964 to 2018. Countries with the most critically endangered fishes are most in need of science. More scientific knowledge is needed on critically endangered fishes to meet the challenges of conserving fishes during the sixth mass extinction.